OPTIMIZATION OF CACAO SEEDLING GROWTH (Theobroma Cacao L.) THROUGH THE INTERACTION OF Asystasia gangetica COMPOST FERTILIZER AND NPK FERTILIZER - Prasatyio, Ahwa Eko; Gusniwati, Gusniwati; Fathia, Nyimas Myrna Elsa; Neliyati, Neliyati (Universitas Jambi, 2025)
Cacao (Theobroma cacao L.) is a widely cultivated plantation commodity. However, its production has declined, with one of the contributing factors being old plants, so rejuvenation must be carried out using high-quality plant seedlings. Good-quality seedlings are obtained through the addition of nutrients during the nursery phase using organic and inorganic fertilizers. This study aims to determine the interaction between Asystasia compost and NPK on seedling growth and to obtain the best dosage of Asystasia compost and NPK on the growth of cacao (Theobroma cacao L.) seedlings. This research was conducted using a Completely Randomized Design (CRD) with a factorial pattern consisting of two factors. The first factor was the dose of NPK fertilizer (P), which consisted of three levels: p0 = 0 g/seedling, p1 = 7 g/seedling, and p2 = 14 g/seedling. The second factor was the dose of Asystasia compost (A), which also consisted of three levels: a0 = 83 g/seedling, a1 = 166 g/seedling, and a2 = 249 g/seedling. There were nine treatment combinations, each repeated three times. In this experiment, cacao seedlings were planted in polybags. The data obtained were analyzed using analysis of variance (ANOVA) to determine the effects, followed by the DNMRT test. The observed variables were seedling height, stem diameter, number of leaves, total leaf area, shoot dry weight, and root dry weight. The results showed that there was an interaction between the application of Asystasia compost and NPK on the variables of seedling height, total leaf area, and shoot dry weight. The application of 166 g/seedling of Asystasia compost and 7 g/seedling of NPK showed the best growth of cacao seedlings in polybags.